Characteristics of Tanning Leather Using Gambir on pH 4 and 8 - Ardinal, Ardinal; Kasim, Anwar; Mutiar, Sri (Biopropal Industri, 2013)
Tannery production process in Indonesia is still using chromium sulfate or mimosa in general. Gambier (Uncaria gambier Roxb.) extract could be used as material for tanners because it contains tannin. This study aimed to investigate the characteristics of tanned leather using gambier solution at pH 4 and 8. Standard tanning method was used which includes the processing of goat leather with salt, acid and then tanned with gambier extracts. Observation of tanned leather refers to the SNI-06-0463-1989-A and ISO 0234:2009. The results showed that characteristics of tanned leather with solution of gambier at pH 4 and 8 respectively i.e.: degrees of tanning 29.87% and 39.55%, tensile strength 279.94 kg/cm2 and 433.85 kg/cm2, leather conditions was limp, light gray colour and yellow, thickness of 0.12 mm and 0.11 mm, and density 0.74 g/cm3 and 0.74 g/cm3. Tanned leather from different pH conditions generally has the same characteristic and meet standards.